THE ROLE OF BLOCKCHAIN IN DIGITAL CREDENTIALS AND THE FUTURE OF EDUCATION CERTIFICATION - Rizki Dewantara; Amin Zaki; Faisal Razak (Journal International Inspire Education Technology, 2026)
Digital transformation has accelerated the adoption of electronic credentials, online certifications, and lifelong learning records across educational institutions worldwide. Growing concerns regarding credential fraud, verification inefficiencies, data security, interoperability, and learner ownership have highlighted the limitations of traditional and centralized certification systems. Blockchain technology has emerged as a promising solution capable of enhancing trust, transparency, and security in educational credential management. This study aims to examine the role of blockchain in digital credentials and explore its implications for the future of education certification. A mixed-methods research design employing a sequential explanatory approach was utilized. Quantitative data were collected from 420 stakeholders, including university administrators, educational technology specialists, employers, policymakers, and graduates. Qualitative interviews were conducted with selected participants to gain deeper insights into implementation opportunities and challenges. Structural Equation Modeling and thematic analysis were employed to analyze the data. Findings revealed that perceived security significantly influenced trustworthiness, while trustworthiness emerged as a strong predictor of adoption intention. Interoperability positively affected institutional readiness and supported efficient credential exchange across educational and professional environments. Qualitative evidence further demonstrated improvements in verification efficiency, credential portability, learner empowerment, and stakeholder confidence. The study concludes that blockchain technology has substantial potential to transform educational certification systems by creating secure, transparent, learner-centered, and globally interoperable credential ecosystems capable of supporting future educational and workforce demands.